Determining Economic Order Quantity for Inventory Control in Distributors of Oil and Lubricant Products - Y Rahmat Akbar; Maraini; Nefrida (CV ODIS, 2023)
This study aims to provide a solution to the problem of inventory control in companies in the procurement of oil and lubricant products. By using the EOQ method, companies can determine optimal purchases to minimize total inventory costs. The results of the study show that the optimal number of orders is 2,743 drums for each order with an ordering frequency of 4-5 times a year. The safety stock is 229 drums and the company must place an order again (reorder point) when the remaining inventory is 454 drums. The total inventory cost incurred by the company is IDR 100 billion with a cost per order of IDR 5.6 billion. It showed that after implementing the EOQ model, it was found that the total cost of the resulting inventory, and from inventory analysis using the economic order quantity model, was successful in making savings compared to before using the economic order quantity model.